Legal Reform in Interfaith Marriage Under Supreme Court Circular No. 2 of 2023 - Nurul Miqat; Safrin Salam; Adfiyanti Adfiyanti; Kayode Muhammad Ibrahim; Abidemi Hassan (Journal of Law and Legal Reform, 2025)
Human nature, being composed of different genders—men and women—naturally drives the attraction and union through marriage, fulfilling the desire to live together. As outlined in Article 1 of Marriage Law No. 1 of 1974, marriage is a physical and emotional bond between a man and a woman as husband and wife, intended to establish a happy and lasting family founded on the principles of God Almighty. Marriage, therefore, holds religious significance, uniting a man and a woman as husband and wife. This study examines the Supreme Court’s decision prohibiting court rulings on interfaith marriages. Using normative research methods, the study analyzes Article 2, Paragraph 1 of the Marriage Law, which states that a marriage is valid if conducted according to the laws of each religion and belief. In response to ongoing debates and increasing pressure due to granted applications for interfaith marriage registration by district courts, the Supreme Court of Indonesia issued Supreme Court Circular Letter No. 2 of 2023. This circular guides judges in adjudicating interfaith marriage applications. The issuance of the circular aims to resolve the controversy surrounding interfaith marriages, which have led to various legal and social issues. Previously, judges based their decisions on Law No. 23 of 2006 on Population Administration, leading to the approval of interfaith marriage applications. However, with SEMA No. 2 of 2023, a clear directive has been established to prevent legal uncertainty and ensure uniformity in court rulings regarding interfaith marriages.